Biomechanical Analysis of Ligatures and Technique for Managing Drainage Tubes in Pediatric Glaucoma. Issue 10 (October 2019) - Adams, Carolina; Kane, Steven; Brooks, Steven E.
Abstract : Purpose: Absorbable ligatures are often used with glaucoma drainage tubes to avoid early postoperative hypotony. We sought to measure the force required to ligate a drainage tube, and develop a modified technique to promote earlier release in pediatric patients, where plate encapsulation occurs more quickly than adults. Methods: A precision digital force gauge was used to measure the tensile strength of several common ophthalmic sutures, and the necessary tensile force required to achieve tube ligation. A novel technique for tube ligation was devised to allow sutures as small as 10-0 to be effectively used. Results: The mean tensile strengths of unknotted sutures varied from 55.50±8.50 g for 10-0 vicryl to 477±69 g for 6-0 chromic gut. The mean tensile force required to ligate a Baerveldt or Ahmed tube was 35.9±0.9 g. However, 9-0 or 10-0 vicryl could not be reliably used for ligation, because of breakage, unless a modified technique was used, wherein the tube was first stretched to reduce its thickness and diameter. Discussion: Frictional forces inherent to knot tying make it unfeasible to reliably use 9-0 or 10-0 vicryl to ligate a drainage tube, despite the unknotted threads possessing apparently sufficient tensile strength. Our modified ligation technique overcomes this issue, allowing a wider range of suture choices, and the potential for achieving more rapid release in pediatric cases.